Persepsi Guru tentang Pemahaman Indikator Standar Pembiayaan Sekolah Menengah Atas - Ossi Marga Ramadhan; Chaerul Rochman; Ida Farida; Supiana Supiana (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2020)
This research was conducted to determine the extent of teachers' perceptions of the standard indicators of financing for high school education at the National Education Standards (SNP). This study used descriptive qualitative method. The population was 10 respondents, divided into 5 Islamic education teacher respondents and 5 Non-Islamic Islamic education teacher respondents from several schools in Purwakarta Regency. The instrument used was to use a questionnaire about understanding the standard of financing, which amounted to 16 indicators, then given triangulation through direct interviews to find out the causes and solutions to problems related to the achievement of financing standards. The results of this study indicate that the achievement of indicators is at an average of 82% in the Non-Islamic Education group and 79% in the Islamic Education group. Several weaknesses were found regarding the standard indicators of financing, among others in the aspect of the realization of the cost of periodic maintenance and repairs and the aspect of reporting and delivering financial accountability. Based on the findings in the field, the researchers have recommendations for schools and related parties to pay more attention to the stages of education financing budgeting, especially during the planning, realization, and reporting stages and submission of financing reports.